2002
DOI: 10.1159/000048637
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Adrenocortical and Gonadal Hormones in Mild to Moderate Alzheimer’s Disease

Abstract: Hormonal changes during normal aging include decreasing levels of gonadal hormones and adrenal androgens. These hormones influence multiple nervous functions, including cognition and mood. Related to this, abnormalities at several levels of the hypothalamic-pituitary-adrenal axis (HPA) have been reported in patients with Alzheimer’s disease (AD). We studied steroid hormones in 33 patients with mild to moderate AD (12 men; 21 women, 76.4 ± 7.8 years) and 22 healthy elderly controls (10 men; 12 women, 75.4 ± 7.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 32 publications
5
56
1
1
Order By: Relevance
“…In subsequent studies by this group, both total (Hogervorst et al, 2004;Hogervorst et al, 2003;Lehmann et al, 2004) and free (Hogervorst et al, 2002) testosterone levels were found to be significantly lower in men without AD irrespective of potentially confounding such indices as age, education, body mass index, smoking, alcohol use, diabetes, and hormone therapy. Similar findings of low testosterone in men with AD have been reported in several (Almeida et al, 2004;Moffat et al, 2004;Paoletti et al, 2004;Rasmuson et al, 2002;Watanabe et al, 2004) but not all (Pennanen et al, 2004) studies. Interestingly, low testosterone has also been linked to several other neurodegenerative diseases, including Parkinson's disease (Okun et al, 2004), vascular dementia (Watanabe et al, 2004), amyotropic lateral sclerosis (Militello et al, 2002), and Huntington's disease (Markianos et al, 2005).…”
Section: Age-related Androgen Depletion and Alzheimer's Diseasesupporting
confidence: 88%
“…In subsequent studies by this group, both total (Hogervorst et al, 2004;Hogervorst et al, 2003;Lehmann et al, 2004) and free (Hogervorst et al, 2002) testosterone levels were found to be significantly lower in men without AD irrespective of potentially confounding such indices as age, education, body mass index, smoking, alcohol use, diabetes, and hormone therapy. Similar findings of low testosterone in men with AD have been reported in several (Almeida et al, 2004;Moffat et al, 2004;Paoletti et al, 2004;Rasmuson et al, 2002;Watanabe et al, 2004) but not all (Pennanen et al, 2004) studies. Interestingly, low testosterone has also been linked to several other neurodegenerative diseases, including Parkinson's disease (Okun et al, 2004), vascular dementia (Watanabe et al, 2004), amyotropic lateral sclerosis (Militello et al, 2002), and Huntington's disease (Markianos et al, 2005).…”
Section: Age-related Androgen Depletion and Alzheimer's Diseasesupporting
confidence: 88%
“…Several studies in the elderly have demonstrated a potentially reversible link between elevated endogenous cortisol levels and decline in memory and frontal-executive abilities (Greendale et al, 2000;O'Hara et al, 2007;Seeman et al, 1997;Li et al, 2006;Beluche et al, 2010;Egeland et al, 2005) and dementia (Umegaki et al, 2000;Rasmuson et al, 2002;Csernansky et al, 2006). Associations between short-term CS administration and cognitive impairment have been reported in small experimental and clinical studies in adults (Wolkowitz et al, 2009;Newcomer et al, 1999;Kirschbaum et al, 1996;Lupien et al, 2007;Young et al, 1999;de Quervain et al, 2003;Keenan et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in plasma cortisol levels have been reported in individuals with probable AD (19,20,21,22,23), but have been generally interpreted as evidence that the disease process of AD (i.e., AD-induced hippocampal degeneration) leads to dysinhibition of the HPA axis. In line with this hypothesis, correlations have been reported between increases in HPA axis activity and dementia severity (24) or hippocampal volume loss (25,26) in individuals with probable AD.…”
Section: Introductionmentioning
confidence: 99%